1997
DOI: 10.1128/mcb.17.6.3295
|View full text |Cite
|
Sign up to set email alerts
|

Abrogation of Interleukin-3 Dependence of Myeloid Cells by the v-src Oncogene Requires SH2 and SH3 Domains Which Specify Activation of STATs

Abstract: The v-src oncogene encodes a nonreceptor tyrosine kinase. When this gene was expressed in the myeloblastic cell line 32Dcl3, it was found to abrogate interleukin-3 (IL-3) dependence of this cell line and to block its ability to terminally differentiate into granulocytes in response to granulocyte colony-stimulating factor (GCSF). In contrast, a highly related tyrosine kinase gene, v-fgr, fails to render this cell line IL-3 independent for growth or to block its ability to undergo terminal differentiation in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
87
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(91 citation statements)
references
References 37 publications
4
87
0
Order By: Relevance
“…IL-3/IL-5/GMCSF activation of hematopoietic cells appears to result predominantly in the activation of JAK-2, although JAK-1 and TYK-2 have also been found to be activated in certain cell systems Quelle et al, 1994;Lutticken et al, 1994;Chaturvedi et al, 1997Chaturvedi et al, , 1998Jaster et al, 1997). The membrane proximal region of the IL-3R b c chain is involved in association with the N-terminal region of JAK2.…”
Section: Stat Signaling Pathwaysmentioning
confidence: 99%
See 1 more Smart Citation
“…IL-3/IL-5/GMCSF activation of hematopoietic cells appears to result predominantly in the activation of JAK-2, although JAK-1 and TYK-2 have also been found to be activated in certain cell systems Quelle et al, 1994;Lutticken et al, 1994;Chaturvedi et al, 1997Chaturvedi et al, , 1998Jaster et al, 1997). The membrane proximal region of the IL-3R b c chain is involved in association with the N-terminal region of JAK2.…”
Section: Stat Signaling Pathwaysmentioning
confidence: 99%
“…These two proteins were originally discovered by Darnell's group in association with STAT-2 and a fourth protein termed p48, which constituted the multicomponent transcription factor ISGF3 (Darnell et al, 1994). STAT-3 also exists in two forms termed STAT3a and STAT3b with di erent transcriptional activation functions (Schaefer et al, 1995;Chaturvedi et al, 1997Chaturvedi et al, , 1998. STAT5 exists in two isoforms, termed as STAT5A and STAT5B (Mui et al, 1995a,b), which are encoded by two separate genes, which are tandemly linked on human chromosome 17 and mouse chromosome 11 (Lin et al, 1996;Copeland et al, 1995).…”
Section: Stat Signaling Pathwaysmentioning
confidence: 99%
“…A recent report has suggested that the mechanism of BCR-Abl-induced STAT activation may be similar to Src (Chaturvedi et al, 1997). Like Src-induced STAT activation, the SH2 and SH3 domains of BCR-Abl are required for constitutive activation of STAT 5 by this oncoprotein (Chaturvedi et al, 1997;NieborowskaSkorska et al, 1999).…”
Section: Activation Of the Jak-stat Pathway By Bcr-ablmentioning
confidence: 99%
“…Like Src-induced STAT activation, the SH2 and SH3 domains of BCR-Abl are required for constitutive activation of STAT 5 by this oncoprotein (Chaturvedi et al, 1997;NieborowskaSkorska et al, 1999). These same studies did not explore the e ect of mutations in the carboxyl terminal portion of BCR-Abl on STAT activation.…”
Section: Activation Of the Jak-stat Pathway By Bcr-ablmentioning
confidence: 99%
“…Src family members may also regulate expression of genes through phosphorylation and activation of transcription factors known as STATs. Recently it was shown that an activated mutant of Src, v-Src, constitutively phosphorylates and activates STAT3, and that STAT3 phosphorylation is necessary for e cient transformation of cells by v-Src (Yu et al, 1995;Cao et al, 1996;Chaturvedi et al, 1997;Bromberg et al, 1998;Turkson et al, 1998). The phosphorylation of STAT3 by v-Src suggests that normal cellular Src may also phosphorylate STAT3 and directly regulate transcription.…”
Section: Introductionmentioning
confidence: 99%